Centralization and decentralization of management in the economy of the USSR in the prewar period (1939 – June 1941): problems of history and historiography - Feldman M.A. (Дискурс Пи, 2020)
The study of the real relationship between centralization and decentralization in the Soviet economy is not only of historical interest. The problem of the role and scope of the state's presence in the economic life of modern Russia has not lost its relevance. The combination of administrative and command methods and economic regulators, horizontal and vertical links between Soviet regions, institutions, and enterprises, and the role of illegal mechanisms for redistributing resources and filling the market remain among the most important areas of historical research. For the first time in the historical literature, this article reveals significant differences in researchers' views on the nature and essence of the Soviet system of government, including in the pre-war and war years. Based on the method of comparative analysis, the conclusion is made that the assessment of the management mechanism as absolutely centralized, based on an immense concentration of power in the center and an authoritarian style of leadership is unreliable. The study was carried out in the framework of the mobilization model of power and socio-economic structure, established in the USSR in the 1920s and 1950s. The conclusion is confirmed that the planned tasks of the people's Commissariat, just like all other agents of the Soviet economy, could change even in the course of their implementation. These changes were both voluntary and forced, and were both legal and illegal. Tasks for people's Commissars could be adjusted as a result of changes in the government's intentions and priorities. It is noted that as a result, the control practice additionally sanctioned violations of the rules and the "shadow" economy. In industry, managers who were risk-averse and resourceful in handling government regulations were rewarded. Managers who could not execute the plan using illegal means, on the contrary, were eliminated. Almost all disputes between business owners at various levels were usually resolved in informal ways, although administrative and judicial means were also available. A similar judgment can be made when assessing the nature of horizontal relations between party bodies and enterprises; there were virtually no formal links between economic commissariats, local authorities, and production organizations.